Mengembangkan Self Regulation dalam Etika Komunikasi - Birowo, Mario Antonius; Perbawaningsih, Yudi (FISIP Universitas Atma Jaya Yogyakarta, 2004)
The existence of codes of conduct in communication field is still interesting to be discussed. Not many practioners and people consider to this conduct while they were doing their jobs. They have major problems in dealing with ethics issues, especially when communicationg in the publics arena. Communications freedom and communications technology are accussed as caustive prima of communications ethics problems. To solve the problem, this article proposes self regulations to control our communication behaviour .